BIOLOGI REPRODUKSI TUMBUHAN PEGAGAN (Centella asiatica) - Nuraini; Ratna Ariyanti; Slamet Mardiyanto Rahayu (Nusadaya Journal of Multidiciplinary Studies, 2025)
This study aims to determine the reproductive biology of the pennywort (Centella asiatica). The methods used were observation and experiments conducted in Kediri Village, West Lombok Regency. The results indicate that Centella asiatica can reproduce both generatively and vegetatively. Generative reproduction occurs through flower formation, pollination, and seed formation, but is not the primary method of reproduction. Vegetative reproduction occurs through stolons, which grow creeping and form new individuals at each node, making them more dominant due to their speed and efficiency. Thus, this reproductive ability demonstrates Centella asiatica's high adaptability to the environment.